2019
DOI: 10.1016/j.cortex.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered frontal and insular functional connectivity as pivotal mechanisms for apathy in Alzheimer's disease

Abstract: Background: Apathy is a common and early symptom in Alzheimer's disease (AD) and is linked to poorer prognosis. Theoretical interpretations of apathy implicate alterations of connections amongst fronto-striatal and limbic regions. Objective: To test the association between presence of apathy and patterns of brain functional connectivity in patients with clinically-established AD. Methods: Seventy AD patients were included. Thirty-five patients experienced apathy as defined by the screening question of the Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 57 publications
1
25
1
Order By: Relevance
“…Although any mechanistic hypothesis would be, at this stage, speculative, it is of central importance to shed light on the map of regional brain damage caused by the virus, because the topography of network dysfunction may account for the onset of chronic behavioural symptoms. A number of studies has shown that the presence of psychiatric symptoms in patients with AD is associated with alterations of brain circuitry (37)(38)(39). If COVID-19 infection damages the neural tissue, it might result into an impoverishment of the neural pathways that support normal psychological functioning and could lead to the onset of cognitive and/or psychiatric dysfunction.…”
Section: Neuropsychiatric Symptoms In People Who Have Contracted Covimentioning
confidence: 99%
“…Although any mechanistic hypothesis would be, at this stage, speculative, it is of central importance to shed light on the map of regional brain damage caused by the virus, because the topography of network dysfunction may account for the onset of chronic behavioural symptoms. A number of studies has shown that the presence of psychiatric symptoms in patients with AD is associated with alterations of brain circuitry (37)(38)(39). If COVID-19 infection damages the neural tissue, it might result into an impoverishment of the neural pathways that support normal psychological functioning and could lead to the onset of cognitive and/or psychiatric dysfunction.…”
Section: Neuropsychiatric Symptoms In People Who Have Contracted Covimentioning
confidence: 99%
“…We used binary NPI scores (symptom present when score >0) similar to other authors (e.g. Jones et al, 2019) as thresholds of clinical significance may vary by symptom (Cummings et al, 1994), and as the nonlinear and skewed frequency × severity score distributions may be problematic in some statistical analyses (Lai, 2014). NPI scores (range 0-144) for each annual measurement can be seen in Table 1.…”
Section: Assessment Of Npssmentioning
confidence: 99%
“…Furthermore, the NPI frequency × severity score requires nonparametric statistical methods (Lai, 2014). Therefore, many authors (recently, e.g., Jones et al, 2019) prefer to use the binary NPI score avoid these issues. Most importantly, individual symptom data are obfuscated when using this compound score.…”
Section: Limitationsmentioning
confidence: 99%
“…Neuroimaging studies of apathy have predominantly focused on individuals with brain diseases or psychiatric conditions, including stroke (Kang and Kim, 2008;Onoda et al, 2011;Rochat et al, 2013;Kumral et al, 2019), neurodegeneration (Apostolova et al, 2007;Marshall et al, 2007;Reijnders et al, 2010;Tunnard et al, 2011;Eslinger et al, 2012;Carriere et al, 2014;Jones et al, 2019), and late-life depression (Lavretsky et al, 2007;Alexopoulos et al, 2013;Yuen et al, 2014). Reviews integrating structural and functional correlates of apathy across different disorders have identified regions commonly associated with apathy, including the anterior cingulate cortex (ACC), ventral striatum (nucleus accumbens; NAcc), thalamus, orbitofrontal cortex (OFC), and insula (IC) (Kos et al, 2016;Le Heron et al, 2018;Pimontel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%